Feasibility of implementing a novel behavioural smoking cessation intervention amongst human immunodeficiency virus-infected smokers in a resource-limited setting: A single-arm pilot trial - Billy M. Tsima; Precious Moedi; Joyce Maunge; Kitso Machangane; Martha Kgogwane; Tebogo Mudojwa; Joseph Bastian; Warren Bilker; Rebecca Ashare; Robert Schnoll; Robert Gross (AOSIS, 2020)
Background: Tobacco use is prevalent amongst individuals infected with human immunodeficiency virus (HIV). In resource-constrained settings, pharmacological smoking cessation interventions are unfeasible because of their high cost. There is a need to develop and evaluate behavioural interventions to address the unique challenges of tobacco use in the HIV-infected populations in these settings. Objectives: The authors aimed to assess the feasibility and acceptability of the Behavioural Activation/Problem Solving for Smoking Cessation (BAPS-SC) intervention programme to determine whether it should be tested in an adequately powered randomised controlled trial. Method: The authors merged behavioural activation therapy (BAT) with the principles of problem-solving therapy to create a novel five-session counselling model to address the unique challenges of tobacco cessation amongst those infected with HIV. Feasibility measures included the rate of enrolment amongst those eligible and the retention rate and descriptive analysis of intervention acceptability. The authors' secondary outcome was 7-day point smoking prevalence abstinence, confirmed with breath carbon monoxide. Results: A total of 128 individuals were screened over 8 weeks with 50 deemed eligible and 40 enrolled (80%). Retention at week 12 was 53% (21/40). The 7-day point prevalence abstinence, co-confirmed, at week 12 was 37.5% (15/40). All respondents indicated that they would recommend BAPS-SC to other smokers who want to quit, and would be willing to participate in the programme again up to the point of exit if they did not stop smoking. Conclusion: A full-scale randomised control trial comparing BAPS-SC with usual practice is warranted to evaluate the efficacy of this novel intervention in these settings.